What Matters for Depression and Anxiety During the COVID-19 Quarantine?: Results of an Online Cross-Sectional Survey in Seoul, South Korea - Kwon, Hye-Young; Kim, Yongjoo; Lee, Seung-Young (Frontiers in Psychiatry, 2022)
Background: Amid the COVID-19 pandemic, quarantine measures are key to containing the spread of the virus. Millions of people have been required to quarantine throughout the pandemic; the quarantine itself is considered detrimental to mental health conditions. Objective: This study aims to investigate the factors associated with depression and anxiety among quarantined people in Seoul, South Korea. Methods: An online cross-sectional survey was administered from October to November 2020 involving people who were living in Seoul, aged 19 years or above, under a 2-week mandatory quarantine. Their mental health status was measured using the Patient Health Questionnaires-9 (PHQ-9) and the General Anxiety Disorder-7 (GAD-7). Results: Overall, 1,135 respondents were finally included, resulting in a 22.0% response rate. After controlling for potential confounders, variables, such as the “second half of quarantine period” (OR=1.78 95% CI: 1.10-2.88), “female” (OR=1.91 95% CI:1.16-3.16), and “having pre-existing depression” (OR=8.03 95% CI:2.96-21.78) were significantly associated with depression while being quarantined. Those with correct knowledge about the rationale behind for the quarantine (OR=0.39 95% CI:0.21-0.72), an understanding of quarantine rules (OR=0.68 95%CI:0.52-0.91), and those who felt supported by others (OR=0.74 95% CI:0.55-0.99) were less likely to develop depression while quarantining. Similarly, anxiety was significantly associated with the second week (OR=4.18 95% CI:1.44-12.09), those with an unstable job status (OR=3.95 95% CI:1.60-9.79), perceived support (OR=0.66, 95% CI:0.45-0.96), and the fear of being infected (OR=7.22 95% CI:1.04-49.95). Conclusions: This study highlights the need to develop precautionary measures to prevent depression and anxiety among people undergoing COVID-19 quarantine. In particular, individuals with depression prior to quarantine should be carefully monitored during the quarantine. Further studies with larger populations are needed.